The effect of emotional security on depressive tendencies in junior high school students: mediation and intervention of interpersonal trust - Li, Xinyue; Chen, Xueqing; Xie, Mengmeng; Zhang, Minghao (Frontiers in Psychology, 2026)
IntroductionEmotional security is closely linked to adolescents’ mental health, yet the mechanisms through which it relates to depressive tendencies remain unclear. This study examined whether interpersonal trust mediates the association between junior high school students’ emotional security and depressive tendencies, and whether box therapy can enhance interpersonal trust and reduce depression-related symptoms.MethodsStudy 1 administered the Emotional Security Scale, the Parental Peer Attachment Scale, and the Depression Scale to 436 students from a junior high school. Study 2 employed a single-subject experimental design, delivering 16 individual box therapy sessions and 8 family box therapy sessions.ResultsEmotional security, interpersonal trust, and depressive tendencies were significantly correlated. Emotional security was negatively associated with depressive tendencies, and interpersonal trust partially mediated the relationship between emotional security and depressive tendencies. In Study 2, the combined individual and family box therapy intervention improved adolescents’ interpersonal trust and showed a beneficial effect in reducing depressive tendency levels.DiscussionInterpersonal trust appears to be a key psychological pathway linking emotional security to depressive tendencies among junior high school students. Box therapy, particularly when integrating individual and family sessions, may be a feasible and practical approach to strengthening interpersonal trust and supporting depression-related symptom reduction in this population.